Peregrinaciones hispanas del «Persée François». Usos panegíricos de un mito, entre Francia y España, en torno a las dobles bodas de 1612-1615 - Roland Béhar (Mélanges de la Casa de Velázquez, 2012)
Traditionally placed in the years 1612-1615, Lope de Vega’s Fábula de Perseo can perhaps be dated, at least as far as its conception is concerned, in 1612. We show that given its subject— a panegyric interpretation of the myth of Perseus―it may have been conceived as a response to the splendid festivities organised in Paris in April 1612, on the occasion of the proclamation of the marriage of Louis XIII and Anne of Austria and of the future Philip IV and Isabella of Bourbon. This interpretation places Lope’s comedy in a European context of political celebrations and makes more sense of it as a panegyric and epithalamium.